Organization capital and executive performance incentives - Gao, Mingze; Leung, Henry; Qiu, Buhui (Journal of Banking & Finance, 2021)
We conjecture that a firm's organization capital (OC) has a substitution effect on its executive pay-for-performance sensitivity (PPS) and empirically document a robust and significant substitution effect of OC on executive PPS. We use state-level unemployment insurance benefits as an instrumental variable for OC and show that the documented OC-PPS substitution effect is likely causal. Results are also robust to a stacked difference-in-differences estimation approach based on a quasi-natural experiment of exogenous CEO turnovers due to health-related issues. Our findings strongly suggest that greater OC substitutes for costly executive incentive compensation to sustain firm productivity and increase shareholder wealth.